Harmonizing neuropsychological assessment for mild neurocognitive disorders in Europe. Issue 1 (13th May 2021) - Boccardi, Marina; Monsch, Andreas U.; Ferrari, Clarissa; Altomare, Daniele; Berres, Manfred; Bos, Isabelle; Buchmann, Andreas; Cerami, Chiara; Didic, Mira; Festari, Cristina; Nicolosi, Valentina; Sacco, Leonardo; et al.
Abstract: Introduction: Harmonized neuropsychological assessment for neurocognitive disorders, an international priority for valid and reliable diagnostic procedures, has been achieved only in specific countries or research contexts. Methods: To harmonize the assessment of mild cognitive impairment in Europe, a workshop (Geneva, May 2018) convened stakeholders, methodologists, academic, and non‐academic clinicians and experts from European, US, and Australian harmonization initiatives. Results: With formal presentations and thematic working‐groups we defined a standard battery consistent with the U.S. Uniform DataSet, version 3, and homogeneous methodology to obtain consistent normative data across tests and languages. Adaptations consist of including two tests specific to typical Alzheimer's disease and behavioral variant frontotemporal dementia. The methodology for harmonized normative data includes consensus definition of cognitively normal controls, classification of confounding factors (age, sex, and education), and calculation of minimum sample sizes. Discussion: This expert consensus allows harmonizing the diagnosis of neurocognitive disorders across European countries and possibly beyond.